Javanese Speech Act at Sabtu Market Tanjung Mulya in Mukomuko: Pragmatic Analysis - Rois Pangestu; Mac Aditiawarman (Fakultas Sastra Universitas Ekasakti, 2023)
This research entitled Javanese speech acts at Sabtu Market Tanjung mulya in Mukomuko: Pragmatic analysis. This study discusses locutionary and illocutionary acts in Traditional Markets. This study aims to analyze the types of locutionary and illocutionary acts used by buyers and sellers at the Sabtu market Tanjung Mulya. The data subject is transactional communication at the Traditional Sabtu Market Tanjung mulya. The theory used in this research is pragmatics, speech acts and classification of speech acts. This research was conducted using descriptive qualitative research. The data analysis technique used descriptive analysis techniques, by describing the types of locutionary and illocutionary acts. The results showed that there were 3 locutionary act concepts used by buyers and sellers, namely: the statement form consisted of 11 findings, the question form had 15 findings, and for the imperative 4 findings. While the illocutionary types are: representative 13 findings, directive 11 findings, commissive 5 findings and expressive 5 findings, declarative findings are not found in this study. It can be concluded that the dominant form of question is used in locutionary and dominant representation is used in illocutionary by buyers and sellers in Traditional Markets